THE ROLE OF SEMIOTIC IN TRANSLATING SYMBOLS FOR BIBLICAL TEXTS - Erfiani, Ni Made Diana; Sukarsih, Ni Nyoman Tri; Susanto, Putu Chris (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2020)
Semiotics, which is the science of signs, has become an increasingly interesting interdisciplinary area of study. As such, semiotics can also be used as both structural and pragmatic approach for translation studies, especially for studies in which meanings are difficult to comprehend including symbolic texts. This paper aims to uncover the role of semiotics in the translation of symbolic languages, especially religious texts. The study employs descriptive qualitative method to describe and interpret the data in the form of an analysis of symbolic text translation. This is to uncover the various attitudes and perspectives about the roles of semiotic science in the translation of religious texts. The findings of this study indicate that the semiotic perspective is able to reveal the dimensions of referential or conceptual meaning of the symbols through the appearance of a supplementary component, which connects literal and figurative meanings conventionally. This effort is carried out through the use of structural semiotic analysis tools, namely by exploring the relationships between symbolic meanings, both syntagmatically and paradigmatically.